Clinical and Haemato-biochemical Characteristics of Hypothyroidism in Canines - Kour, Harneet; Chhabra, Sushma; Randhawa, Charanjit S. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Hypothyroidism is one of the common endocrine disorders of dogs. The present study was conducted from June 2018 to February2020 at Small Animal OPD of the University, Ludhiana, Punjab. The hospital prevalence of hypothyroidism was found to be 0.174%(35/20102). The mean total thyroxine level (0.44 ± 0.61 µg/dL) in hypothyroid dogs was significantly (p ≤0.01) lower, whereas themean thyroid-stimulating hormone (TSH) level (6.79 ± 0.01 ng/mL) was significantly (p ≤0.01) higher as compared to healthy dogs.The most common clinical characteristics associated with hypothyroidism were metabolic signs, particularly lethargy (51.43%), obesityor weight gain (80.08%), exercise intolerance (68.57%) and dermatological abnormalities including bilateral alopecia (85.71%), rat tailappearance (71.42%), hyperpigmentation (28.57%), pruritus and poor coat quality (14.28% each). The haemato-biochemical changesincluded elevated TLC, hypercholesterolemia, hyper-triglyceridemia, significantly higher ALP, hypocalcemia, and hypophosphatemia.These results confirmed that thyroid hormones play a significant role in maintaining the body's metabolic equilibrium and the integrityof different organs, such as the liver, kidney, and skin.
Keywords: Dogs; Hypercholesterolemia; Hypothyroidism; Thyroid-stimulating hormone; Thyroxine